An Unconfident Public: Explaining Perceptions of the 2016 Presidential Nominations. Issue 3 (19th March 2021) - Jewitt, Caitlin E.
Abstract: Using an AP‐NORC survey, I analyze the impact of the electoral rules, voter demographics, and perceptions of the 2016 nominations on confidence in the fairness of the presidential nominations. I reveal that perceptions of outsider candidates affect confidence in the parties' processes. Believing that superdelegates are a good idea is associated with feeling more confident. Also, when citizens experience an electoral environment that matches what they believe to be the fairer rule, higher levels of confidence in the fairness of the processes result. These findings matter not only in their own right, but also for the potential influence on participation, the legitimacy of democracy, and party decisions about nominating rules.